Penguatan Kapasitas Wirausaha Kerajinan Handmade Melalui Digitalisasi dan Pelatihan SDM - Vava, Muhammad Akhva Aulia N; Lazuardi, Muhammad Lazuardi F; Pranoto, Henry Susanto; Sitepu, Rismawati (Apik Cahaya Ilmu, 2024)
This research aims to improve creativity and production capacity in sustainable handicrafts by utilizing artificial intelligence (AI)-based technology as a step towards achieving the Sustainable Development Goals (SDGs). The methods applied include exposure and training on AI technology, as well as skills development designed to encourage increased creativity and productivity of local craftsmen. By using software such as Pebblely and Visionate, craftsmen can improve the efficiency and quality of products and production processes. In addition, these solutions help ensure consistent quality and increase the ability to meet market demand more effectively. This initiative is also in line with efforts to achieve the SDGs, especially in poverty alleviation and improving the welfare of local communities. By empowering the skills and creativity of craftsmen through the application of AI-based technology, as well as promoting the principles of SDGs, it is hoped that Handmade House can be an example of sustainable and inclusive local economic development